Characterization and Combustion Kinetics of Binderless and Bindered Dry Cow Dung Bio-Pellets - Wibowo, Wusana Agung; Susanti, Ari Diana; Paryanto, Paryanto (Equilibrium Journal of Chemical Engineering, 2024)
The effect of molasses addition as a binder in the manufacturing of cow dung bio-pellets on their characteristics and combustion kinetics have been studied. The bio-pellets characterization included the physical and mechanical properties as well as the proximate analysis and calorific values. Thermogravimetric analysis (TGA) was carried out using a macro-TGA apparatus under a non-isothermal conditions and an oxidative atmosphere to study the thermal decomposition characteristics. Then, the first order Coast and Redfern method was used to determined the kinetic parameters of bio-pellets combustion. It was found that the ash content of bio-pellets were tended to decreased, while the volatile matter and fixed carbon were tended to increase with the addition of molasses. Nevertheless, the density, the axial compressive strength and the calorific values of bindered bio-pellets were decreased due to the higher amounts of water in the raw mixtures. Thermogravimetric analysis provided an information that the combustions of cow dung bio-pellets took place in three stages of decompositions The bindered bio-pellet began to decompose at lower temperatures than the binderless bio-pellet with a higher weight loss percentage. According to the comprehensive combustion characteristic index (S), the combustion performance of both binderless and bindered bio-pellets were similar. The addition of molasses as a binder tended to reduce the ignition temperature and activation energy for all stages of bio-pellets combustion. Keywords:Bio-pellet, Characterization, Cow Dung, Combustion Kinetics, Molasses